2018
DOI: 10.1016/j.evolhumbehav.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Early life conditions, reproductive and sexuality-related life history outcomes among human males: A systematic review and meta-analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 114 publications
(163 reference statements)
4
46
0
Order By: Relevance
“…However, here are also studies that failed to find some of the theoretically expected associations: e.g. the absence of the relations between the age at first menarche and reproductive success (Hochberg, Gawlik, & Walker, 2011) or the lack of association between family socioeconomic status and pubertal timing (Xu, Norton, & Rahman, 2018). This is a consequence of the immense complexity of human populations and a great variability between the populations as well.…”
Section: Life History Theorymentioning
confidence: 81%
“…However, here are also studies that failed to find some of the theoretically expected associations: e.g. the absence of the relations between the age at first menarche and reproductive success (Hochberg, Gawlik, & Walker, 2011) or the lack of association between family socioeconomic status and pubertal timing (Xu, Norton, & Rahman, 2018). This is a consequence of the immense complexity of human populations and a great variability between the populations as well.…”
Section: Life History Theorymentioning
confidence: 81%
“…We conclude that the inconsistent relationship of family SES with pubertal timing probably reflected inherent differences in study populations such as ethnic and geographic variations, gender and genetic predisposition and changes in underlying mechanisms influenced by SES to activate puberty such as intrauterine conditions, health, nutrition, stress and environmental exposures (Parent et al 2003). Other methodological issues including differences in study designs and measurement of SES and pubertal timing indicators (Xu et al 2018) might have contributed to this inconsistency.…”
Section: Summary and Interpretation Of Resultsmentioning
confidence: 91%
“…In contrast, recent evidence revealed that low family SES markedly increased rates of early puberty in both boys and girls (Downing and Bellis 2009;Sun et al 2017), possibly through interactions with biological systems regulating pubertal timing (Sun et al 2017) or other risk factors such as having a higher body mass index (BMI) or being overweight (Downing and Bellis 2009;James-Todd et al 2010) and experiencing stressful life events (James-Todd et al 2010). However, a meta-analysis of studies among males found no significant association between family SES and pubertal timing (Xu et al 2018). Since there is limited research on determinants of pubertal onset among boys, the processes influencing male pubertal development were much less understood (Graber 2013).…”
Section: Summary and Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported associations between developmental environment and adult traits are rarely controlled for genetic confounders (e.g. in twin-family designs) (McAdams et al 2014;Zietsch 2016;Barbaro et al 2017;Sherlock and Zietsch 2017b;Sherlock and Zietsch 2017a;Xu et al 2017), and when they are controlled the associations are often weaker or null (Mendle et al 2006;Mendle et al 2009;McAdams et al 2014; though see Tither and Ellis 2008). In light of these observations, a perspective focussed on adapted responses to early environmental conditions does not seem promising as a broad framework for explaining human trait covariation (Zietsch 2016).…”
Section: Genetic Coadaptation Vs Adapted Developmental Plasticitymentioning
confidence: 99%